War, peace and pollen: examining the landscape of later medieval Wales - Davies, Tudur (Medieval Settlement Research, 2022)
This paper presents the second part of a review of palynological studies covering the medieval period in Wales. The first part, covering the period c. AD 410–1050 (Davies 2019), has been published in Comeau and Seaman’s edited review of medieval agriculture in Wales (2019); the current paper examines the period c. AD 1050–1500. Although some scholars have previously examined palynological trends in Wales through the earlier medieval period (e.g. Dark 2000; Rippon et al. 2013; 2015; Davies 2015; 2019; Rippon 2019), the later medieval period has been relatively neglected in regional reviews of palaeoenvironmental data. The greatest contribution has been provided by Astrid Caseldine (cf. Edwards 1997; Roberts 2006), who has demonstrated the potential of such research with her work on cores from Ynys Etws (Caseldine 2006), Llyn Morwynion (Caseldine et al. 2001) and several other sites. The current review builds on Caseldine’s work, providing a comprehensive examination of published pollen studies and considering the potential cultural influences on Wales’ pollen record.